2017
DOI: 10.17159/2310-3833/2016/v46n3a4
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality in the occupational therapy community fieldwork process: A qualitative study in the South African context

Abstract: Background: Spirituality is an integral part of communities; it is influenced by the environment and provides

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…It was evident the use of technology facilitated occupational adaptation, as older adults were able to connect with others using a variety of social media platforms such as WhatsApp to video call church friends and receive sermons. In accordance with occupational adaptation, the findings of the meta-synthesis indicated that the older adults developed a sense of competence, self-efficacy, and identity, which corroborate other studies 60,63,64,65 . This process of dynamic occupational adaptation by the older adults speaks to a higher degree of resilience to environmental barriers.…”
Section: Discussionsupporting
confidence: 86%
“…It was evident the use of technology facilitated occupational adaptation, as older adults were able to connect with others using a variety of social media platforms such as WhatsApp to video call church friends and receive sermons. In accordance with occupational adaptation, the findings of the meta-synthesis indicated that the older adults developed a sense of competence, self-efficacy, and identity, which corroborate other studies 60,63,64,65 . This process of dynamic occupational adaptation by the older adults speaks to a higher degree of resilience to environmental barriers.…”
Section: Discussionsupporting
confidence: 86%
“…In the absence of believing in the supernatural, people tend to perceive spirituality as a motivating force, integrating mind, body and spirit (Mthembu et al, 2018). Similarly, Hess and Ramugondo (2014) and Mthembu et al (2017b) agree that spirituality provokes and nourishes 'human volition as a basis for action' and that engaging in spiritual activities in the community are motivating and health promoting. Likewise, occupational therapy students perceived that spiritual occupations are motivating and associated with coping styles, motivation and satisfaction with life (Misiorek & Janus, 2019;Mthembu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…By recognising the individuality and uniqueness of clients, occupational therapists can develop clientcenteredness in their everyday practice. Mthembu et al (2017b) explored spirituality in community fieldwork practice and concluded that spirituality was a core element of communities, emphasising that occupational therapy practice should involve awareness of the spiritual needs of communities.…”
Section: Discussionmentioning
confidence: 99%